PENGARUH MOTIVASI BELAJAR DAN METODE PEMBELAJARAN TERHADAP PRESTASI BELAJAR MAHASISWA PROGRAM STUDI KOMPUTERISASI AKUNTASI POLITEKNIK LP3I JAKARTA KAMPUS BLOK M” - Asmawi Mangku Alam (Majalah Ilmiah Bijak, 2016)
This study was taken from the thesis that aims to analyze how big Influence of Motivation and Learning Method of the Achievement of Student Learning Program Computerized Accounting Polytechnic LP3I Jakarta Campus Blok M "study was conducted that indicated that student achievement of students having a bit of trouble and it was suspected because they elmahnya motivation and learning methods dilakukakan by students concernedThe sampling method used is the technique of sampling Sampling saturated namely by taking them as a population of 50 samples. Data that has met the test of validity and reliability further processed to produce a regression equation Y = 0.850 + 0645 + 0117 X2 X1, which wherein Y is variable learning achievement, X1 is a variable of learning motivation and X2 is variable learning methodMotivation to learn is partially positive effect on learning achievement indicated by the r value of 0.682, which means a strong relationship between them. The learning method is partially positive effect on learning achievement indicated by the r value of 0.458 which means the relationship between them is very strong. Variables simultaneously teaching and learning media capabilities have a significant impact on the learning citizen satisfaction shown by the r value of 0.687 which means the relationship between them is very strong. While the coefficient of determination R-square value of 0, 4719, which means that the variation of all the independent variables that motivation to learn and learning methods may explain the variable student achievement by 47.19%, while the remaining 52.81% is explained by other variables that are not submitted within this research.